IL10 Low-Frequency Variants in Behçet's Disease Patients - Matos, M (2016)
To explain the missing heritability after the genome-wide association studies era, sequencing studies allow the identification of low-frequency variants with a stronger effect on disease risk. Common variants in the interleukin 10 gene (IL10) have been consistently associated with Behçet's disease (BD) and the goal of this study is to investigate the role of low-frequency IL10 variants in BD susceptibility.